2020
DOI: 10.3390/nu12092654
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzed Rice Protein-Based Formulas, a Vegetal Alternative in Cow’s Milk Allergy

Abstract: Formulas adapted to infant feeding, although most of the time made from cow’s milk proteins, can be made from hydrolyzed rice protein but they must be classified as “formulas for specific medical needs”, according to European regulations. The nutritional quality of rice proteins is thus suitable to be used in infant formulas giving that it is supplemented by certain amino acids which can be lacking. Besides, hydrolysis is required to facilitate their water solubility and digestibility. Owing to a low allergeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 68 publications
0
48
0
Order By: Relevance
“…Rice-based HF are tolerated by at least 90% of CMA-allergic children, as recently addressed [ 29 ]. Notewothy, most of the clinical studies assessing rice-based formula were conducted on children with IgE-mediated CMA [ 30 , 31 , 32 ]. Only two studies were conducted on both IgE-mediated and non-IgE-mediated CMA, both of which confirmed the high tolerability of this formulation even in non IgE CMA [ 26 , 33 ].…”
Section: Hydrolysed Cow’s Milk and Vegetable Protein-based Formulas: Tolerance Nutritional Value And Palatabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Rice-based HF are tolerated by at least 90% of CMA-allergic children, as recently addressed [ 29 ]. Notewothy, most of the clinical studies assessing rice-based formula were conducted on children with IgE-mediated CMA [ 30 , 31 , 32 ]. Only two studies were conducted on both IgE-mediated and non-IgE-mediated CMA, both of which confirmed the high tolerability of this formulation even in non IgE CMA [ 26 , 33 ].…”
Section: Hydrolysed Cow’s Milk and Vegetable Protein-based Formulas: Tolerance Nutritional Value And Palatabilitymentioning
confidence: 99%
“…Hence, rice HF are generally supplemented with these three amino acids [ 39 ]. Rice protein hydrolysis is required to improve water solubility and digestibility [ 30 ]. Soy formulas may have a lower absorption of minerals and trace elements due to their phytate content.…”
Section: Hydrolysed Cow’s Milk and Vegetable Protein-based Formulas: Tolerance Nutritional Value And Palatabilitymentioning
confidence: 99%
“…The nutritional quality of rice proteins is suitable to be used in infant formulas giving that it is supplemented by certain amino acids that can be lacking. 83 Infants fed a RHF for 6 months showed normal growth, normal plasma nutritional parameters and no adverse reactions. [84][85][86] No significant differences between RHF, soy infant formula and casein EHF groups were observed for the z-score for weight-for-age during the first two years of life.…”
Section: Plant-based Based Infant Formulamentioning
confidence: 85%
“…It is not a quick process to change HCP prescribing behavior, as evidenced by the length of time it has taken for HRF to become mainstream practice in some European countries. Indeed, HRF is currently marketed mainly in Italy, France, and Spain [6].…”
Section: Expert Presentation: Practical Experience Using Hrf From a Gastroenterologist's Perspectivementioning
confidence: 99%
“…Cow's milk allergy (CMA) is the most common food allergy in early childhood, and approximately 80% of children will outgrow it by 3-5 years of age [4,5]; its prevalence ranges from 1.9% to 4.9% [6]. It manifests through a variety of symptoms that place a significant burden on the infant and caregiver alike [7].…”
Section: Introductionmentioning
confidence: 99%